Membangun Generasi Peduli Laut melalui Edukasi Pentingnya Ekosistem Pesisir di Desa Tanjung Bunga - Fatmawati Fatmawati; A. Ginong Pratikino; Risfandi Risfandi; La Ode Muhammad Arsal; Muhammad Trial Fiar Erawan; La Ode Adi Parman Rudia (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Indonesia's coastline is home to various complex ecosystems, such as mangroves, coral reefs, and seagrass beds. These ecosystems are very important in maintaining marine biodiversity and supporting the economic activities of local communities. One of the main problems that conservation efforts for coastal ecosystems face is the low level of environmental knowledge and awareness among local communities, especially among the younger generation. This activity aims to give students an understanding of how important marine ecosystems are through a participatory educational approach while simultaneously raising awareness about how human behavior impacts the sustainability of coastal resources. The results of this activity showed an increase in student understanding as evidenced by their ability to re-explain the concepts of mangrove, seagrass, and coral reef ecosystems their ecological functions and threats plus their ability to provide concrete examples on the role of coastal ecosystems in maintaining environmental stability. In terms of awareness regarding ecological threats students can mention various damage factors like pollution mangrove logging and uncontrolled tourism activities.